Jamming Attacks Reliable Prevention in a Clustered Wireless Sensor Network - Valencia-Cordero, C (Springer New York LLC, 2015)
A heterogeneous wireless sensor network attacked by jamming is analyzed as a two-player non-cooperative game chance constrained problem, the utility function is based on the signal interference plus noise ratio at the receiver. In view of the problem’s stochasticity, second order cone programming is used to solve the game problem. Our preliminary numerical results show that the communication distance between network elements must be taken into account at the time of establishing the design requirements of any reliable application against jamming attacks. Furthermore, it is established that the receiver’s sensitivity level is a central parameter for changing the frequency used for the power transmission initially selected by the nodes. © 2015, Springer Science+Business Media New York.
Keywords: Wireless sensor network; Jamming attack; Chance constraints; Second order cone programming; Game theory